Teachers engaged in research : inquiry into mathematics classrooms, grades 6-8 - Masingila, Joanna O. 1960- (Teachers engaged in research., 2006)
Through the chapters in this volume we learn about the research foci and/ or questions that these classroom teachers are interested in examining, the mathematics content through which they engaged their students in these explorations, the data sources they used to make sense of their focus and questions, and their roles in the research.